Economic Transformation: How Does the Agricultural Sector Performance in Indonesia's Regional Economic Structure? - Asrilis Boy Saban; Sahara; A. Faroby Falatehan (Department of Development Economics, Universitas Sriwijaya, 2023)
This study aims to analyze the performance of the agricultural sector on the structure of the regional economy in Indonesia. The data used is secondary data in the form of the 2016 Indonesian Inter-Regional Input-Output Table, classified for 52 sectors and 34 provinces. Contribution analysis in the IRIO approach is used to answer research objectives. The research results show that the agricultural sector in producing output, allocating input to other sectors, providing final demand, absorbing the output of other sectors, and forming primary input in each region in Indonesia has different contributions. These different contributions are adjusted to the resource potential of each region. In particular, the agricultural sector in North Maluku Province has a significant role in the economic structure of North Maluku. The North Maluku agricultural sector has a contribution in producing output, providing final demand, absorbing intermediate inputs, and forming primary inputs that are higher than the average contribution of other provinces in Indonesia.